Macrocyclic glycopeptide-based chiral selectors for enantioseparation in sub/supercritical fluid chromatography - Folprechtová, Denisa; Kalíková, Květa (Analytical science advances, 2021)
Increasing number of reported works dealing with macrocyclic glycopeptide-based columns in sub/supercritical fluid chromatography (SFC) points to the growing interest in this area. With the development and production of sub 2 µm fully porous particles and superficially porous particles with bonded macrocyclic glycopeptides, significant improvements have been made in ultrafast high efficiency chiral SFC. This review article gives an overview of macrocyclic glycopeptide-based chiral selectors that were used in theoretical studies and/or applications in SFC. The review covers the period from 1997 when macrocyclic glycopeptides were first used in SFC till the end of July 2020 according to Web of Science. This work can also be helpful to analysts searching for an appropriate method for the separation/determination of enantiomers of their interest.
Keywords: macrocyclic glycopeptide; chiral stationary phase; enantioseparation; sub/supercritical fluid chromatography